Routine assessment of cognitive function in older patients with hypertension seen by primary care physicians: why and how—a decision-making support from the working group on 'hypertension and the brain' of the European Society of Hypertension and from the European Geriatric Medicine Society. Issue 1 (January 2021) - Scuteri, Angelo; Benetos, Athanasios; Sierra, Cristina; Coca, António; Chicherio, Christian; Frisoni, Giovanni B.; Gasecki, Dariusz; Hering, Dagmara; Lovic, Dragan; Manios, Efstathios; Petrovic, Mirko; Qiu, Chengxuan; et al.
Abstract : N/A: The guidelines on hypertension recently published by the European Societies of Hypertension and Cardiology, have acknowledged cognitive function (and its decline) as a hypertension-mediated organ damage. In fact, brain damage can be the only hypertension-mediated organ damage in more than 30% of hypertensive patients, evolving undetected for several years if not appropriately screened; as long as undetected it cannot provide either corrective measures, nor adequate risk stratification of the hypertensive patient. The medical community dealing with older hypertensive patients should have a simple and pragmatic approach to early identify and precisely treat these patients. Both hypertension and cognitive decline are undeniably growing pandemics in developed or epidemiologically transitioning societies. Furthermore, there is a clear-cut connection between exposure to the increased blood pressure and development of cognitive decline. Therefore, a group of experts in the field from the European Society of Hypertension and from the European Geriatric Medicine Society gathered together to answer practical clinical questions that often face the physician when dealing with their hypertensive patients in a routine clinical practice. They elaborated a decision-making approach to help standardize such clinical evaluation.